Drug Coated Balloon only Angioplasty Outcomes in Non-diabetic and Diabetic Patients with De Novo Small Coronary Vessels Disease - Muhammad Israr, Quratulain, Huma Naeem Tareen, Asma Hameed, Tufail Ijaz, Muhammad Rehan Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Small artery coronary disease is a known predictor of terrible outcomes after PCI, and it is quite challenging to identify the best course of action for treating coronary disease in small vessels. Objective: The aim of this study was to explore the Drug-Coated Balloon-Only Angioplasty Outcomes in Non-diabetic and Diabetic patients with De Novo Small Coronary Vessels Disease. Methodology: This correctional multi-centre study was carried out at the Cardiology Department BMCH Quetta and Cardiology department Al Qasimi hospital Sharjah, UAE from January, 2023-June, 2023 after taking permission from the ethical board of the institute. Over all 1200 participants with vascular disorder cured with Drug-Coated Balloon -Test method were examined. Angiographic and clinical follow-up were scheduled for 12 months. The key outcomes were non-primary large detrimental cardiac activities and target lesion failure. Both the 2-tailed Fisher’s actual test and chi-squared test were used to assess express variables, and the unbiased samples t-test (also known as the "Student’s t-test") was used to assess non-stop variables. When the bilateral P is less than 0.05, it is deemed statistically significant. Results: A total of 1200 participants were enrolled in this study out of which 832(69.33%) were male and 368(30.6%) were female. 431(35.9%) were diabetes and 769 (64.0%) were non diabetic. A total of 1352 lesions were treated; 484 were identified within the diabetes treatment group and 869 among the non-diabetic group. In the diabetes and non-diabetic groups, standard artery thickness was comparable (P value 0.366); however, the operating voltage inflation level and period were also comparable (P value 0.416 and 0.474, correspondingly).There have been notable differences in TLF incidence costs between companies, with a higher incidence among the diabetic population (P value0.006). There have been no statistically significant variations of the MACE comparing many of the two firms (P value 0.120). Conclusion: Our study concluded that the drug-covered balloon alone decreased the incidence of target lesion failure and significant detrimental cardiac events in patients with de novo small coronary artery disease. Keywords: Drug-Coated Balloon; Angioplasty; Non-diabetic; Diabetic; Coronary Vessels Disease.